The state of the human capital of Russia under the present conditions - A. R. Almukhametova (Путеводитель предпринимателя)
In modern conditions, to increase the growth ofbasic economic indicators, it is necessary to use and rationally use all available resources and resources, including human resources. The purpose of this article is to study the state of the use of human capital in the country.